Cone-beam computed tomography evaluation of the root morphology of the maxillary and mandibular premolars in a Moroccan subpopulation: Canal configurations and root curvatures (Part 2) - Said Dhaimy; Sara Dhoum; Manal Diouri; Lamyae Bedida; Hafsa Elmerini; Imane Benkiran (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this study is to investigate canal configurations and root curvatures of maxillary and mandibular premolar teeth in a Moroccan subpopulation using cone-beam computed tomography (CBCT) images. Materials and Methods: The root curvature and canal configuration of 919 CBCT images of maxillary (358) and mandibular (561) premolar teeth were investigated using "Planmeca viewer" software. Data were analyzed using descriptive statistics. Results: About 46.8% of the maxillary first premolars with two roots had Type I canal configuration of each roots and 27.5% of single-rooted ones presented Type VII. The two-rooted maxillary second premolars showed Type I (39.35%) canal configuration. As for the single-rooted premolars, 32.8% showed Type III canal configuration. The distobuccal curvature was the most frequent for the single-rooted teeth (30.4%) as well as for the palatal (32.4%) root of the two-rooted ones. More than 70% of each root, had Type I of the two rooted mandibular first premolars while 41.8% of the single-rooted premolars had Type V. Type I canal configuration was the most revealed in single-rooted mandibular second premolars with a percentage of 60.6%. Few teeth with two and three roots were seen. The distolingual curvature showed the highest incidence among single-rooted premolars (37.8%) as well as the buccal roots of the two-rooted ones (51.8%). Conclusion: The Moroccan subpopulation's premolars showed a high prevalence of Vertucci's canal configuration Type I with distobuccal curvature for maxillary teeth and distolingual for mandibular teeth.